IMPLEMENT AN EXTENSION CORD POWER SOCKET WITH EMERGENCY LIGHTING AND VOICE CONTROL LIGHTING FUNCTIONS - Wang, Ching-Sung; Liu, Chien-Wei; Wang, Teng-Hui (International Journal of Research -GRANTHAALAYAH, 2017)
Conventional power sockets are equipped with an extension cord. Even with anti-overload devices, incidents of accidental discharge or damage to electrical appliances may still incur due to external factors. To address this problem, this study integrated the voice control and lighting functions to the design of the power socket with an extension cord. The proposed design is space-efficient and versatile, and can be used in living rooms, bedrooms, and other places having electrical appliances. The proposed design also integrated emergency lighting and flashlight functions, so as to expand the practicality and safety of the power socket.